2006
DOI: 10.1007/s10654-006-9029-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of respiratory drug use in the Lombardy region of Italy, 1995–1997

Abstract: The definition of specific drug use patterns by individual can provide prevalence measures that are broad proxies for varying categories of respiratory disease. However, a very high proportion of people who receive respiratory drugs do so for one-off or very infrequent episodes of illness. Analysis of the infrequent and more regular users of respiratory drugs may be useful for comparative research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…However, an Italian study of drug coverage in the registry concluded that the data was considered representative and sufficiently complete for large patient populations. 36 The absence of an effect of the SEP on adherence to drug therapy, observed in the present study, supports this assumption. A critical issue in drug adherence studies is the choice of the drug consumption measure.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, an Italian study of drug coverage in the registry concluded that the data was considered representative and sufficiently complete for large patient populations. 36 The absence of an effect of the SEP on adherence to drug therapy, observed in the present study, supports this assumption. A critical issue in drug adherence studies is the choice of the drug consumption measure.…”
Section: Resultssupporting
confidence: 84%
“…This practice is more common among patients of the higher socio‐economic classes. However, an Italian study of drug coverage in the registry concluded that the data was considered representative and sufficiently complete for large patient populations 36 . The absence of an effect of the SEP on adherence to drug therapy, observed in the present study, supports this assumption.…”
Section: Resultssupporting
confidence: 73%